Gonadotropin-releasing hormone analogue and recombinant human growth hormone treatment for idiopathic central precocious puberty in girls - Shi, Yuzhen; Ma, Ziyi; Yang, Xi; Ying, Yanqin; Luo, Xiaoping; Hou, Ling (Frontiers in Endocrinology, 2022)
Abstract Purpose: To investigate the effectiveness and safety of gonadotropin-releasing hormone analogue (GnRHa) in combination with recombinant human growth hormone (rhGH) in girls with central precocious puberty (CPP). Methods: Clinical data of 80 girls diagnosed with idiopathic central precocious puberty (ICPP) between January 2017 and June 2021 were retrospectively analyzed. Treatment strategy involved GnRHa alone (group A: n=34) and GnRHa+rhGH (group B: n=46). Children’s heights (Ht), weights (Wt) and sex hormone levels were measured every 3 months after treatment and bone age (BA) every six months. Heights, growth velocity (GV), predicted adult height (PAH), weights, body mass index (BMI), sex hormone levels and bone age were compared between the two groups. Results: Children in group B showed greater height gain at the 12th, 24th and 30th months after treatment (p<0.05) than those in group A, had faster growth rates in the first and second year following treatment (p<0.05) and better PAH (p<0.05). No statistical differences in weight or BMI were found between the two groups before treatment or at any time after treatment (p>0.05). Levels of LH and FSH were lower in both groups after treatment with no statistical differences between groups (p>0.05). The gap between bone age and chronological age gradually decreased in both groups and no abnormal progression of bone age or other adverse side effects occurred. Conclusions: The combination of GnRHa with rhGH produced better height gains than GnRHa alone for patients with CPP. The gonadal axis was suppressed and progression of bone age delayed with good safety and efficacy.